Microdomain homogeneity evaluation of perpendicular lamellar structures in block copolymer films: X-ray scattering and IR nanospectroscopy analyses - Wooseop Lee (Elsevier, 2021)
Self-assembled block copolymer (BCP) thin films necessarily require a distinct chemical contrast between the blocks (or microdomain homogeneity) for the purpose of high-resolution pattern transfer applications. Despite its importance, however, there has been difficulty in measuring the chemical distribution associated with the self-assembling processes, i.e. solvent vapor annealing (SVA) or thermal annealing (TA). Herein, we present a simple yet effective method to probe the chemical distribution over polystyrene-b-poly(methyl methacrylate) (PS-b-PMMA) films that underwent the SVA or SVA + TA processes. An IR nanospectroscopy using scattering-type scanning near-field optical microscopy (s-SNOM), in concert with X-ray scattering analyses, provides the relative chemical concentration of the perpendicular lamellar patterns. The chemical mapping for the components based on the s-SNOM reveals that the SVA process leaves a considerable portion of the intermixed zones of PS and PMMA blocks, whereas the subsequent TA process facilitates the chain segregation towards high-contrast chemical distribution. Interestingly, such a microdomain homogeneity critically affects the quality of the unidirectional Al2O3 lines that were substituted from topographically guided lamellae. Our results substantiate an important insight into understanding the chain redistribution behavior in the self-assembled BCP films using non-destructive s-SNOM technique.